The Effect of Infographic Media Assisted by Aural Text on Improving Understanding of the Fiqh of Worship in Elementary School Students - Fitria Tahta Alfina; Achmad Nur Mustofa; Deni Setiawan (Jurnal Penelitian Pendidikan, 2023)
This research investigates the influence of infographic media assisted by aural text on the understanding of fiqh worship among elementary school students. The research method employed is an experimental design with a Posttest-Only Group Design. The data were collected using probability sampling and cluster sampling techniques and gathered through observations, interviews, documentation and tests. Data analysis was conducted using a t-test. The study's results, which involved 34 students at MI Darul Ulum, indicate that the use of infographic media assisted by aural text significantly improves the understanding of fiqh worship among students in Grade III A as the experimental group. In contrast, the understanding of students in Grade III B as the control group shows less significant improvement. Based on these findings, it can be concluded that the use of infographic media assisted by aural text is effective in enhancing students' understanding of fiqh worship, emphasizing the importance of media in religious education at the elementary school level, and providing significant implications for the development of more innovative and effective teaching methods in the future.